Unhealthy Friendships Affect the Mental Health of Students - Agustina, Nur Hikmah; Madya, Efi Brata (FORUM PAEDAGOGIK, 2025)
This study aims to understand the impact of unhealthy friendships on the mental health of students in the Islamic Guidance and Counseling Study Program at the Faculty of Da'wah and Communication, State Islamic University of North Sumatra for the Academic Year 2021, as well as the adaptive strategies applied to cope with such toxic relationships. The research method uses a descriptive qualitative approach with purposive sampling, data collection through in-depth interviews, observation, and documentation, and data analysis conducted interactively and continuously. The results of the study indicate that toxic friendships are characterized by manipulative behavior, social and academic jealousy, and emotional exploitation, which lead to increased stress, anxiety, decreased self-esteem, and emotional fatigue among students. Students develop adaptive strategies in the form of setting personal boundaries, reflection and strengthening emotional awareness, seeking healthy social support, and reinforcing religiosity as coping mechanisms. These findings confirm that the quality of friendships has a significant impact on students' mental health and emphasize the importance of guidance and counseling-based interventions, particularly through the approach of Islamic values, to build healthy social relationships and support psychological well-being